IMPROVEMENT OF VERIFICATION AND EVALUATION STUDENTS’ KNOWLEDGE - Buhriy, O.V. (Pedagogy of Higher and Secondary Education, 1999)
To increase the guality of pupils’ knowledge we must improve the control and appraisal of learning this knowledge. The article deals with the guestions of content of control and the criterias of appraisement as well as the problems of the main point of control and appraisal, the accounting of results, the standard of knowledge. Creative using ofacguired knowledge are stressed by the author.